2017
DOI: 10.13075/mp.5893.00430
|View full text |Cite
|
Sign up to set email alerts
|

Fatal accidents at work in agriculture associated with alcohol intoxication in Lower Silesia in Poland

Abstract: Background: Determining the prevalence of alcohol intoxication and the level of intoxication in victims of fatal occupational accidents is necessary to improve work safety. The circumstances of the accident and the time between alcohol consumption and death are important factors. Material and Methods: A retrospective review of 18 935 medico-legal autopsy reports and toxicological reports performed in the Department of Forensic Medicine at the Wroclaw Medical University, Poland, in the years 1991-2014. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, performance may as well be related to contextual performance (such as working extra hours and helping coworkers), counterproductive behaviour (such as workplace aggression and property damage) and issues related to job safety, such as injuries resulting from accidents (p. 132) 5. A recent Norwegian study revealed that employees’ alcohol consumption was a major concern relating to safety issues,33 and several studies support an association between alcohol and occupational injuries 34–36. However, in the context of the present review, we focused on work performance related to task performance, which can be conceived of as most directly related to on-the-job productivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, performance may as well be related to contextual performance (such as working extra hours and helping coworkers), counterproductive behaviour (such as workplace aggression and property damage) and issues related to job safety, such as injuries resulting from accidents (p. 132) 5. A recent Norwegian study revealed that employees’ alcohol consumption was a major concern relating to safety issues,33 and several studies support an association between alcohol and occupational injuries 34–36. However, in the context of the present review, we focused on work performance related to task performance, which can be conceived of as most directly related to on-the-job productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-related presenteeism (impaired work performance associated with alcohol consumption) has been identified as an under-researched topic in the research literature (Thørrisen et al, 2019). Evidence supports the view that employee alcohol consumption may be associated with impaired work performance (Jurek & Rorat, 2017; Schou, 2016). Due to low research quality and lack of longitudinal designs, existing evidence should still be characterised as inconclusive regarding the prevalence, nature, and impact of alcohol-related presenteeism in the workforce (Thørrisen et al, 2019).…”
Section: Economic Evidence For Interventions Supporting Well-being To...mentioning
confidence: 71%
“…Evidence supports the view that employee alcohol consumption may be associated with impaired work performance (Jurek & Rorat, 2017;Schou, 2016). Due to low research quality and lack of longitudinal designs, existing evidence should still be characterised as inconclusive regarding the prevalence, nature, and impact of alcohol-related presenteeism in the workforce (Thørrisen et al, 2019).…”
Section: Alcohol Misusementioning
confidence: 99%
“…In a study conducted in Portugal (18), one in four fatally injured farm tractor drivers was under the influence of alcohol. Many studies confirm that alcohol is a leading risk factor for work-related injuries (23,24) as slightly intoxicated people and people under the influence of alcohol tend to become more daring, bolder and inclined towards making poor decisions. The higher frequency of drunk farm tractor drivers in our country can be culturally explained, given that drinking alcoholic beverages in our region has been traditionally accepted and culturally approved.…”
Section: Discussionmentioning
confidence: 99%